The Evaluation of the Success about House Nutrition in Improvement Nutrition Status in Semarang - Hasana, Dien; Baitul Mukarromah, Siti (Universitas Negeri Semarang, 2019)
Nutrition is an important factor that directly affects the quality of human resources, health problems and childhood nutrition is a major factor inhibiting the achievement of quality generation. Profile data Semarang City Health Office (2017), cases of malnutrition children year 2013-2016 showed a rising trend. Semarang City Health Office have children malnutrition treatment programs in a comprehensive manner, ie checks and supplementary feeding for malnourished children under five in the